2018
DOI: 10.4103/sni.sni_45_18
|View full text |Cite
|
Sign up to set email alerts
|

Review of the neurological benefits of phytocannabinoids

Abstract: Background:Numerous physical, psychological, and emotional benefits have been attributed to marijuana since its first reported use in 2,600 BC in a Chinese pharmacopoeia. The phytocannabinoids, cannabidiol (CBD), and delta-9-tetrahydrocannabinol (Δ9-THC) are the most studied extracts from cannabis sativa subspecies hemp and marijuana. CBD and Δ9-THC interact uniquely with the endocannabinoid system (ECS). Through direct and indirect actions, intrinsic endocannabinoids and plant-based phytocannabinoids modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
108
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 125 publications
(155 reference statements)
0
108
1
4
Order By: Relevance
“…2b) and dN/dS ratios (5). Contrary to the hypotheses of Onofri et al (3), these findings 20 suggest that divergence at CBDAS loci rather than THCAS loci are primarily responsible for the THCA/CBDA ratio. We estimated genome-wide ancestry proportions of CBDRx to be 89% marijuana and 11% hemp.…”
Section: Main Textcontrasting
confidence: 66%
See 1 more Smart Citation
“…2b) and dN/dS ratios (5). Contrary to the hypotheses of Onofri et al (3), these findings 20 suggest that divergence at CBDAS loci rather than THCAS loci are primarily responsible for the THCA/CBDA ratio. We estimated genome-wide ancestry proportions of CBDRx to be 89% marijuana and 11% hemp.…”
Section: Main Textcontrasting
confidence: 66%
“…When decarboxylated to THC and CBD, these molecules bind to endocannabinoid receptors in the nervous systems of 5 vertebrates and elicit a broad range of neurological effects in humans (1). Cannabinoid receptor types CB1 and CB2 preferentially bind THC and CBD, respectively, with CB1 being among the most abundant post-synaptic neuron receptor in the human brain whereas CB2 is more prevalent in the peripheral nervous system (2)(3)(4)(5)(6)(7). Archeological and forensic evidence suggests that the 10 psychoactivity of THC played a role in early domestication (8)(9) and in selective breeding to increase marijuana potency during the late 20th century (2).…”
Section: Main Textmentioning
confidence: 99%
“…But the cannabis plant contains more than 400 chemicals, including cannabidiol. 8 Cannabidiol, which accounts for up to 40% of the plant extract, does not cause the euphoria induced by THC 8 and is legal in the UK. Indeed, cannabidiol-containing oils, food and drinks are increasing popular.…”
Section: Complex Chemistrymentioning
confidence: 99%
“…THC elicits psychoactive effects but also has shown medical benefits, particularly for neurologic disorders . In contrast, CBD can help to moderate and subdue the psychosis‐inducing effects of THC .…”
mentioning
confidence: 99%
“…6 THC elicits psychoactive effects but also has shown medical benefits, particularly for neurologic disorders. 7,8 In contrast, CBD can help to moderate and subdue the psychosis-inducing effects of THC. 9 Although research is ongoing, combinations of THC and CBD have shown benefit for neurodegenerative diseases such as multiple sclerosis, glaucoma, pain management, food intake disorders, involuntary motor disorders, schizophrenia, and sleep conditions.…”
mentioning
confidence: 99%